2019
DOI: 10.1186/s41100-019-0215-x
|View full text |Cite
|
Sign up to set email alerts
|

Multipotentials of new asymmetric cellulose triacetate membrane for on-line hemodiafiltration both in postdilution and predilution

Abstract: Background: On-line hemodiafiltration (OL-HDF) has been generally provided mainly by the postdilution method in Europe and the rest of the world; however, in Japan, it has been provided mostly by the predilution method in order to ameliorate dialysis-related symptoms of dialysis patients by removing larger low molecular weight proteins. This study aimed to elucidate the removal properties of a newly launched asymmetric triacetate (ATA) membrane in OL-HDF both in the postdilution and predilution comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…The removal performance of the middle molecules increases as the substitution volume increases in the same dilution mode, and comparing the dilution modes, post-OHDF is superior to pre-OHDF. This result resonates with that of previous studies [20].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The removal performance of the middle molecules increases as the substitution volume increases in the same dilution mode, and comparing the dilution modes, post-OHDF is superior to pre-OHDF. This result resonates with that of previous studies [20].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, β 2 -MG, with a molecular weight of 11,800, was thought to be removed mainly by diffusion rather than by filtration. This is consistent with the findings of previous reports that compared the removal performance of pre-and post-OHDF [5,20]. As β 2 -MG is removed mainly by diffusion, it would be insufficient to attribute the improvement in mortality resulting from OHDF to β 2 -MG removal only.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the albumin leakage in the membrane we employed was well defined. Given that the membrane used in this study did not cause excessive transmembrane pressure or significant albumin leakage [18], our results indicated that post-dilution OL-HDF does not significantly impact the concentration of ionized magnesium and calcium when albumin leakage is limited to approximately 5 g/session.…”
Section: Discussionmentioning
confidence: 76%